Event Discrimination Using Phase Correlation in Φ-OTDR System Based on Coherent Detection - Zhen Zhong; Feng Wang; Xuping Zhang (IEEE Photonics Journal, 2018)
We report a novel method of event discrimination using phase correlation in Φ-OTDR system based on coherent detection. The phase change demodulated from the Rayleigh backscattering light is the result of the event acting on the optical fiber. Then, the correlation coefficient between the phase change of every point along the fiber and that of the fiber end is obtained. A vibration event acting on the fiber induces the change of the correlation coefficient. So, the number of vibration events is determined by the number of changes of the correlation coefficient. In addition, it proves that our proposed method is able to discriminate two close events even when they are in the range of half-pulsewidth.